Identification of the Antifungal Metabolite Chaetoglobosin P From Discosia rubi Using a Cryptococcus neoformans Inhibition Assay: Insights Into Mode of Action and Biosynthesis - Perlatti, Bruno; Nichols, Connie B.; Lan, Nan; Wiemann, Philipp; Harvey, Colin J. B.; Alspaugh, J. Andrew; Bills, Gerald F. (Frontiers in Microbiology, 2020)
Cryptococcus neoformans is an important human pathogen with limited options for treatments. We have interrogated extracts from fungal fermentations to find Cryptococcus-inhibiting natural products using assays for growth inhibition, differential thermosensitivity, and synergy with existing antifungal drugs. Extracts from fermentations of strains of Discosia rubi from eastern Texas showed anticryptococcal bioactivity with preferential activity in agar zone of inhibition assays against C. neoformans at 37 °C versus 25 °C. Assay-guided fractionation led to the purification and identification of chaetoglobosin P as the active component of these extracts. Genome sequencing of these strains revealed a biosynthetic gene cluster consistent with chaetoglobosin biosynthesis and β-methylation of the tryptophan residue. Proximity of genes of the actin-binding protein twinfilin-1 to the chaetoglobosin P and K gene clusters suggested a possible self-resistance mechanism involving twinfilin-1 which is consistent with the predicted mechanism of action involving interference with the polymerization of the capping process of filamentous actin. A C. neoformans mutant lacking twinfilin-1 was hypersensitive to chaetoglobosin P. Chaetoglobosins also potentiated the effects of amphotericin B and caspofungin on C. neoformans.